PENERAPAN PENDEKATAN JELAJAH ALAM SEKITAR PADA PERKEMBANGBIAKAN TUMBUHAN DI SEKOLAH DASAR - toyo, Ismar; Indriasih, Aini (HUMANIKA, 2013)
THE APPLICATION OF NATURE EXPLORATION APPROACH TO TEACH PLANTS GENERATION IN ELEMENTARY SCHOOLS ABSTRACT The Nature Exploration Approach is one of innovative approaches in teaching natural science and natural study which scientifically employ natural surroundings and stimulation as learning sources with students-centered learning. The Nature Exploration Approach emphasizes a closer relationship between the students’ learning and real world life to enlarge students’ knowledge. This approach enables students to learn various concepts and relate them to real world life so that the students learning achievement is effective. This study adopts the Nature Exploration Approach and employ a one-group quasi-experiment design with a pretest and a posttest. The subjects of this research are 27 sixth-year students of Jurang 2 Elementary School at Kecatamatan Gebog of Kudus Regency. The finding shows the score of individual activeness is 85 which is categorized as very active. The learning mastery score is 88.03 of homogeneous category. Using Anova, the value of sig (=0,000) < α (=0,05 is found. Students’ Learning activeness has a linear relationship with students’ learning achievement. The score of R² ( R square) = 0,648 indicates that students’ activeness influences students’ learning achievement as much as 64.8% and other factors influence it as much as 35,2%. With the score of sig (=0,000) < α (=0,05) and the score of R² ( R square)=0,616, it indicates that process skills affect students’ achievement as much as 61,6%, and other factors influence it as much as 38,4%. Using A t-test, the t-observed of pre-test and post-test is 12.2 with sig of 0,000=0% < 5%. The findings shows that there is a significant difference between the students achievement before and after the treatment employing the Natural Exploration Approach. Key Words: The Nature Exploration Approach, Science Achievement, plants generation